Steel is Changing the Los Angeles Skyline - Johnston, Roy G. (Engineering Journal, 1964)
Visitors to the city of Los Angeles recently have noticed a great change in the character of the city. Today, tall multistoried structures are projecting above the skyline—many twenty story buildings, some thirty stories, and at least one in the design stage of forty-five stories. Construction records are being broken daily. Prior to 1957, the city was flat; the important building structures were "box-like", all apparently the same height. By law, the buildings were limited to thirteen stories and not more than 150 ft in height.